2023
DOI: 10.1002/lary.30993
|View full text |Cite
|
Sign up to set email alerts
|

Molecular Factors in Carcinoma Ex Pleomorphic Adenoma: Systematic Review and Meta‐Analysis

Seraphina Key,
Clemente Chia,
Zubair Hasan
et al.

Abstract: ObjectiveCarcinoma ex pleomorphic adenoma (CXPA) is a rare malignant salivary gland tumor. Although multiple reviews have been published on salivary gland malignancies, it has been a decade since the last dedicated systematic review pertaining to CXPA alone was published. This study examines molecular factors in CXPA diagnosis.Data SourcesMEDLINE, CINAHL, Embase, Scopus, Web of Science (BIOSIS), Cochrane CENTRAL, Health Collection (Informit), OpenDOAR, and GreyNet International.Review MethodsSystematic review … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 86 publications
0
4
0
Order By: Relevance
“…In a recent systematic review and meta-analysis focusing on the molecular factors involved in the diagnosis of CXPA was conducted by Key and colleagues. 95 This study identified important biomarkers such as p53, PLAG1, and PTEN. 95 Similarly, our results showed CNA in the miR-NAs p53, PLAG1 and PTEN genes.…”
Section: Discussionmentioning
confidence: 96%
See 1 more Smart Citation
“…In a recent systematic review and meta-analysis focusing on the molecular factors involved in the diagnosis of CXPA was conducted by Key and colleagues. 95 This study identified important biomarkers such as p53, PLAG1, and PTEN. 95 Similarly, our results showed CNA in the miR-NAs p53, PLAG1 and PTEN genes.…”
Section: Discussionmentioning
confidence: 96%
“…95 This study identified important biomarkers such as p53, PLAG1, and PTEN. 95 Similarly, our results showed CNA in the miR-NAs p53, PLAG1 and PTEN genes. This may support the role of these genes in the pathogenesis of this pathology and reinforces that these target genes are not only the result of genetic alterations but also of epigenetic alterations.…”
Section: Discussionmentioning
confidence: 96%
“…Similarly, PTEN mutations/deletions characterize a subset of the Carcinoma ex pleomorphic adenoma (CXPA). Additionally, hyalinising clear cell carcinoma (HCCC) subtype demonstrate similar genetic signatures (50,51). In conjunction, another genetic analysis in secretory myoepithelial carcinomas (SMCA) -a very rare, signet ringlike mucinous carcinoma with a myoepithelial componentrevealed very specific and unique PTEN mutation and splicing variant (c.655C>T p. Q219*, and c.1026+1G>A p. K342, respectively) (52).…”
Section: Pten Alterations In Sgcsmentioning
confidence: 98%
“…The conventional belief is that the majority of primary parotid tumors (75% -85%) are benign, with pleomorphic adenoma (PA) and Warthin tumor (WT) accounting for up to 93% of benign parotid tumors (1)(2)(3)(4). However, PA is not so innocent and harmless because carcinoma ex pleomorphic adenoma (CXPA), a malignant salivary gland tumor typically found in the parotid gland, arises from the "benign" tumor PA (5)(6)(7). Early on, this tumor appears benign.…”
Section: Introductionmentioning
confidence: 99%